(untitled) (LACCEI, 2024)
Abstract – The urban agglomeration of Lima and Callao is the second largest city in the world located in a desert, and its supply depends on three small rivers, the Rímac River being the one with the greatest water supply, affected by contamination by mining tailings, sewage and Solid waste. In order to know the climatological and hydrographic conditions that favor the concentration of heavy metals in the water, the relationship between rainfall, water discharges and concentration of aluminum, cadmium, iron and lead in the Rímac River hydrographic system in the period 2018 – 2021. For which data processing was carried out from six meteorological stations, a water quality monitoring point and four limnimetric stations, through dynamic tables. As a result, it was found that the concentration of heavy metals is higher in the lower basin when rainfall and river level increase in localities of the Alto Rímac sub-basin, which presents intense mining activity, unlike the Santa Eulalia sub-basin. river where there are no large-scale mining operations, whose records present weaker relationships with the concentration of heavy metals. In conclusion, the highest concentration of heavy metals in the lower basin occurs during the months with the most intense rains in the headwaters of the basin, as the dragging capacity increases during the flooding of rivers and streams, allowing concentrations to exceed up to 120 times the quality standards for the production of drinking water.